2017
DOI: 10.1002/cncr.30592
|View full text |Cite
|
Sign up to set email alerts
|

Impact of an alternative chromosome 17 probe and the 2013 American Society of Clinical Oncology and College of American Pathologists guidelines on fluorescence in situ hybridization for the determination of HER2 gene amplification in breast cancer

Abstract: Reflex testing with an alternative chromosome 17 probe using the 2013 ASCO/CAP guidelines reclassified 28.1% of tumor samples that had CEP17 CNA, converting nearly one-half from equivocal to amplified. The benefit of HER2-targeted therapy in this patient population requires further study. Cancer 2017;123:2230-2239. © 2017 American Cancer Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 41 publications
3
27
0
Order By: Relevance
“…6 Alternate chromosome 17 reference probes may aid in establishing the true HER2 status. [6][7][8][9] Unfortunately, the current guidelines do not offer a definite recommendation for the specific use of the probes, nor do they provide guidance for which particular probe to use. Here we describe our institutional experience using D17S122 for reflex FISH testing on double-equivocal invasive breast carcinomas and review the literature on double-equivocal HER2 cases with a focus on FISH evaluation using alternate reference probes for determining HER2 status.…”
Section: 2mentioning
confidence: 99%
See 3 more Smart Citations
“…6 Alternate chromosome 17 reference probes may aid in establishing the true HER2 status. [6][7][8][9] Unfortunately, the current guidelines do not offer a definite recommendation for the specific use of the probes, nor do they provide guidance for which particular probe to use. Here we describe our institutional experience using D17S122 for reflex FISH testing on double-equivocal invasive breast carcinomas and review the literature on double-equivocal HER2 cases with a focus on FISH evaluation using alternate reference probes for determining HER2 status.…”
Section: 2mentioning
confidence: 99%
“…A number of studies [6][7][8][9]27 used alternate reference probes for chromosome 17 in an attempt to clarify the true status of HER2 and chromosome 17 in breast carcinomas and the comparative utility of the CEP17 probe. Genomic studies 28,29 have shown chromosome 17 polysomy to be a rare event in breast carcinomas.…”
Section: Fish For Her2 Using Alternate Reference Probesmentioning
confidence: 99%
See 2 more Smart Citations
“…The most commonly used FISH assay is the dual-probe assay, 1 fluorescently labeled probe hybridizing to the target HER2 gene, and 1 probe hybridizing to the centromeric region of chromosome 17 on which the HER2 gene is located. 5 The latter probe, CEP17, is used as a surrogate marker for the chromosome 17 number, and thus increased CEP17 signals above a certain threshold are considered to indicate the presence of polysomy 17. 6 However, recent studies with broader genomic approaches, including comparative genomic hybridization and multiplex ligation-dependent probe amplification, have demonstrated the rarity of true polysomy in breast cancers, and increased CEP17 signals were thought to be due to the pericentromeric amplifications.…”
mentioning
confidence: 99%